Pengaruh pemahaman TRI Pantangan Tamansiswa, sikap moral dan tingkat kepercayaan terhadap niat melakukan penyelewengan pajak - Dewi Kusuma Wardani Wardani; Yuli Prihatni; Ayu Wulandari (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2022)
Taxes as the main source of state revenue have not yet reached the target. Factors causing the low achievement of tax revenue are tax evasion, tax avoidance and the many cases of tax fraud. Therefore, is it necessary to increase knowledge about tax fraud from an early age and the factors that can influence the intention to commit tax fraud. The study aims to examine effect of understanding tri pantangan Tamansiswa, moral attitude and trust in intention to commit tax fraud. Sample in this research is Students Majors Accountancy at Sarjanawiyata Tamansiswa Yogyakarta University. The sample in this study is determined by sampling convenience method, the data collected with distribution questionnaires. The data analysis technique uses descriptive statistics. Based on the result of the study indicate that understanding tri pantangan Tamansiswa and moral attitude has negative on intention to commit tax fraud. Trust has no influenceon on intention to commit tax fraud.